Legal Culture of Public Servants: The Comparative Legal Analysis of the Formation Practices of Various Countries - ALIMBEKOVA, Mira A.; IBRAYEVA, Alua S.; ICHSHANOVA, Gulnar T.; USEINOVA, Karlygash R.; IBRAYEV, Nurlan S. (Journal of Advanced Research in Law and Economics; Vol 10 No 7 (2019): JARLE Volume X Issue 7(45) Winter 2019DO - 10.14505/jarle.v10.7(45).02, 2019)
The legal culture of public servants is determined by the fact that the legislation implements a mechanism for the formation of a moral component, which allows to limit the use of punitive measures and at the same time ensure compliance with the law in the framework of public administration processes. The relevance of the study is determined by the fact that a public servant, in addition to following state standards for dealing with citizens, must also follow the general social culture of observing the rule of law. The novelty of the study is determined by the fact that as the main component in the formation of the legal culture of public servants, it is necessary to consider the implementation of law and the corresponding moral standard directly in the legislation and, based on this position, implement practical activities both within the framework of the public administration system and within the framework of public interaction. The authors investigate the theoretical aspects of the implementation of this provision in the legislation of the countries of the Euroregion, Kazakhstan and the United States. The article shows that the main impact on the legal culture of public servants here is exerted by norms that are implicit in the legislation. The practical significance of the study is determined by the fact that the theoretical model under study will make it possible to adopt basic regulations on the basis of the principles of sustainability of the society functioning and to adopt the concept of development of the rule of law.